RESOLUTION OF THE EXPERT FORUM OF RUSSIAN FEDERATION "CHICKENPOX: SERIOUS INFECTION IN RUSSIAN FEDERATION, WHICH CAN BE PREVENTED DUE TO VACCINATION" DECEMBER 7, 2019 (Вопросы современной педиатрии)
.